Multiple essential roles for primary cilia in heart development - Willaredt, Marc August; Gorgas, Karin; Tucker, Kerry (Cilia, 2012)
The primary cilium is a microtubule-based, plasma membrane-ensheathed protrusion projecting from the basal bodies of almost all cell types in the mammalian body. In the past several years a plethora of papers has indicated a crucial role for primary cilia in the development of a wide variety of organs. We have investigated heart development in cobblestone, a hypomorphic allele of the gene encoding the intraflagellar transport protein Ift88, and uncovered a number of the most common congenital heart defects seen in newborn humans.